A new species of Amitermes silvestri from Amapá state, Brazil (Isoptera, Termitidae, Termitinae) - Constantino, Reginaldo (Museu Paraense Emilio Goeldi, 2016)
The soldier and worker castes of Amitennes aporema, sp.n., are describedfrom material collected in the cerrado vegetation of eastem Amapá State, Brazil. Drawings of the soldier head and worker mandibles are presented.